Fiscal Decentralization and the Efficiency of Public Service Delivery - Sow, Mousse; Razafimahefa, Ivohasina (Washington, D.C. : International Monetary Fund, 2015)
This paper explores the impact of fiscal decentralization on the efficiency of public service delivery. It uses a stochastic frontier method to estimate time-varying efficiency coefficients and analyzes the impact of fiscal decentralization on those efficiency coefficients. The findings indicate that fiscal decentralization can improve the efficiency of public service delivery but only under specific conditions. First, the decentralization process requires adequate political and institutional environments. Second, a sufficient degree of expenditure decentralization seems necessary to obtain favorable outcomes. Third, decentralization of expenditure needs to be accompanied by sufficient decentralization of revenue. Absent those conditions, fiscal decentralization can worsen the efficiency of public service delivery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet